Ecofisiologia química de espécies nativas de dois biomas do estado do Paraná - Pilatti, Daiane Maria (2012)
Allelopathy is an ecological phenomenon defined as the chemical, positive or negative interference of compounds produced by plants on growth and development of other plants. This phenomenon can modify the structure of plant communities, significantly influencing processes such as ecological succession and species dominance. However, the production of compounds is often affected by environmental conditions, and the allelopathic response of the same species can be differentiated depending on the habitat that is. Thus, the objective of this study was to assess whether different forest types within the State of Paraná can influence the allelopathic effect of native plant species recommended for restoration. The plant species were collected from two forest types: semideciduous forest and Tropical Rainforest. Representing the group of pioneer species were collected J. micrantha, C. and M. pachystachya bimucronata; The group was composed of secondary species by species S. terebinthifolius and C. fissilis; climax species was chosen as the E. edulis. The chemical composition of the collected individuals and allelopathy on germination and early development of pioneer species in secondary and climax species, and secondary, in the climax species, simulating the ecological succession that occurs in the field was analyzed. Species showed differences in the concentration of allelopathic compounds, but the species S. terebinthifolius was the only one to present qualitative difference between chemical compounds. It was found that these species may show differences in potential allelopathic effect and, depending on the forest type in which they were collected, mainly as to speed germination and seedling height field. Finally, the collected species in semideciduous forest were more chemically aggressive than the same species collected in Dense Forest, within the State of Paraná